Digitizing menu design management to enhance nutrition consultation services quality at Tefa Nutrition Care Center (NCC), Jember State Polytechnic - Ayu Febriyatna; Firda Agustin; Ratih Putri Damayati; Erna Selviyanti (Community Empowerment, 2024)
Nutrition Care Service (NCC) is part of the TEFA pilot program at Jember State Polytechnic, operating within the care service sector with the objective of meeting clients' nutritional needs and providing systematic solutions to nutritional issues. One of the nutrition services offered by TEFA NCC is menu planning for patients. The goal of this service is to digitize menu design to streamline nutrition consultations at TEFA NCC, Jember State Polytechnic. The stages involved include problem identification, application design and development, Forum Group Discussion (FGD), and monitoring and evaluation of activities. The obtained results include a website that is fully prepared for managing patient menus digitally, streamlining the process for counselors to create meal plans, achieving an efficiency rate of 83%.